Relationship Between Psychological Factors and Entrepreneurial Intentions of University Undergraduates in North East, Nigeria - Inuwa, Bello Mohammed; Mohammed, & Danjuma Ibrahim (Journal of Technical Education and Training, 2017)
The purpose of the study was to determine the psychological factors predicting entrepreneurial intentions of University undergraduate students. The design for the study was a correlation survey design. The area for the study covered all Federal Universities of Technology in North East Nigeria, with a population of 3700, when split, 2000 and 1700 are from ATBU, Bauchi and MAUTECH, Yola respectively. Stratified proportionate sampling technique was employed to arrive at 348 students, using Krejcie and Morgan table for determining sample. When split, 188 and 160 students are from ATBU and MAUTECH respectively. Two structured questionnaires, namely, PFQ and EIQ used for data collection were adapted from four different authors. The PFQ comprises of 41, while the EIQ contains 12 items. Results obtained in the pilot tested questionnaires revealed Cronbach’s alpha of PFQ and EIQ to be 0.784 and 0.730 respectively. Data collected were analyzed using SPSS (Version 20). Findings of the study revealed that all the three independent variables were found to be significant with the dependent variable, as well as all variables combined were found to have been positive in predicting the dependent variable. Finally, conclusions were reached and recommendations made.